Antimicrobial potency assay of common antibiotics collected from different drug stores in Dhaka Metropolis - Modak, Biswajit; Rahman, Md Shahinur; Gazi, Mohammad Shahid; Uddin, Md Aftab; Rahman, Tasmina (Stamford Journal of Microbiology, 2015)
Antibiotic, known as the magic bullet, was developed to control the growth of pathogenic bacteria. Efficacy of an antibiotic depends on its target site on bacteria. The current public health issue is the emergence of resistant bacterial strains against these drugs. The present study was undertaken to perform the routine antibiotic susceptibility pattern of eight laboratory isolates (Escherichia coli, Bacillus spp., Staphylococcus spp., Vibrio spp., Salmonella spp., Pseudomonas spp., Klebsiella spp. and Listeria spp.) against eleven different categories of antibiotics (Ciprofloxacin, Cephradine, Metronidazole, Cefuroxime, Cefixime, Levofloxacin, Amoxicillin, Azithromycin, Doxycycline, Erythromycin and Flucloxacillin) available in local markets of Dhaka metropolis. Among these antibiotics, Azithromycin, Ciprofloxacin, Cefuroxime, Levofloxacin and Doxycycline showed the highest potency against these bacteria. On the contrary, Amoxicillin and Metronidazole showed almost no potency. Erythromycin, Cephradine and Flucloxacillin gave variable effectivity against the tested isolates. These findings reveal that measures for prevention and containment of antimicrobial resistance are necessary in Bangladesh. DOI: http://dx.doi.org/10.3329/sjm.v3i1.22749 Stamford Journal of Microbiology, Vol.3(1) 2013: 26-29